Comparative Analysis of Microbial Growth in Raw and Pasteurized Cow and Camel Milk During Chilled Storage - Mohammed Aladhadh; Emad M. Abdallah (Journal of Pure and Applied Microbiology)
Camel milk has been an integral component of diets in the Middle East for millennia. The current study aimed to evaluate microbial changes in pasteurized camel and cow milk using culture-based methods. We examined bacterial growth in raw and pasteurized camel and cow milk during 17 days of refrigerated storage at 4 °C. Raw camel milk had a mean initial bacterial count of 4.13 × 10³ CFU/mL, peaking at 2.87 × 106 CFU/mL by day 17. Pasteurization reduced the count to 2 × 10¹ CFU/mL, rising to 40 × 104 CFU/mL by day 17. Raw cow milk started at 1.08 × 104 CFU/mL, reaching 3.15 × 106 CFU/mL, while pasteurized cow milk increased from 31.12 CFU/mL to 4.06 × 106 CFU/mL. Coagulase-positive Staphylococcus aureus and Lactobacillus spp. exhibited significant proliferation in raw camel and cow milk. The growth reached a high point of 5.27 × 104 CFU/mL for coagulase-positive S. aureus and 3.74 × 104 CFU/mL for Lactobacillus spp. in raw camel milk. In raw cow milk, it reached a high point of 1.20 × 105 CFU/mL for coagulase-positive S. aureus and 5.0 × 105 CFU/mL for Lactobacillus spp., these results show that these microorganisms grow in different ways in camel milk and cow milk. This shows how vulnerable raw milk is to microbial growth. Pasteurized samples showed no S. aureus or Lactobacillus spp. growth, confirming pasteurization’s effectiveness. The study detected no fungal or pathogenic contamination. In conclusion, camel milk exhibited higher initial bacterial counts and slower bacterial growth than cow milk, but supported more sustained microbial proliferation over time. Pasteurization was equally effective for both types, eliminating Lactobacillus spp. and reducing bacterial loads significantly.